Optimization of stingless bee propolis extractions and comparison of chemical composition and biological activity - Khamsah Suryati, Mohd; Nur Basyirah, Md Zin; Azierah, Azemin; Muhammad Muslim, Mohd Rodi (2017)
Propolis has been used as therapeutic agent since ancient time and considered as high value materials. In order to obtain maximum yield of extract production with excellent biological activity, extraction techniques need to be optimized. This study aimed to optimize extraction protocol and screen total phenolic, total flavonoid and antioxidant activity. Propolis was collected from Apiary of UniSZA, Besut Campus and extracted with 70% and 95% of ethanol using different extraction methods which were: maceration, sonication and soxhlet. The total phenolic and flavonoid contents were determined using spectrophotometric method. Antioxidant activity was evaluated by DPPH assay. Effectiveness of extraction methods were compared based on extraction yield, total metabolite (total phenolic and flavonoid) and antioxidant activity. Propolis extraction by 4 hours soxhlet using 95% ethanol produced the highest yield at 49.29%. However, extraction by sonication at 10 minutes of 70% ethanolic extract showed the highest total phenolic content of 16.98 ± 0.10 mg gallic acid equivalents/g extract propolis (GAE/g). While 70% ethanolic extract from 30 minutes of sonication method displayed the highest total flavonoid content as compared to that of 95% ethanol with value of 107.27±4.10 mg quercetin equivalents/g extract (QE/g). The lowest total flavonoid content was 95% ethanolic extract by soxhlet extraction at 2 hours (18.65 ± 0.47 QE/g). The propolis extract of 95% ethanol from sonication (30 minutes) showed a good antioxidant activity with IC 50 value of 11± 0.55 mg Trolox equivalents/g extract. In the present study, propolis extracted by 30 minutes sonication period showed the most efficient to obtain extract with good phenolic content, flavonoid content and antioxidant activity than those two other methods. Finding from this study also showed that specification of extraction method is important to yield high quality extract.